THE RELATIONSHIP OF MOTHER'S BEHAVIOR REGARDING BALANCED NUTRITION WITH NUTRITIONAL STATUS OF THE CHILDREN AT ELEMENTARY SCHOOL NO. 98 IN NORTH CITY OF GORONTALO - fitrichia a.k. naue; sofyan tambipi; srikit s. nurkamiden (Jurnal Ilmiah dr. Aloei Saboe, 2021)
Until now, the problem of balanced nutrition related to nutritional status is still a problem that is quite often discussed and maternal behavioral factors are considered influential in this situation. Therefore the knowledge, attitudes and actions of mothers about balanced nutrition need to be reviewed more deeply. The study aims to determine the relationship between maternal behavior regarding balanced nutrition and the nutritional status of the children at Elementary School No. 98 in North City of Gorontalo. The method in this research is correlational quantitative. The sampling technique used accidental sampling with a total sample of 30 respondents. The data was collected using a questionnaire and analyzed using the Spearman Rank correlation test with a significant value of = 0.05. The result shows that most of the mother's knowledge and mother's actions about balanced nutrition were sufficient for 11 respondents (36.7%), while the mother's attitude about balanced nutrition was good for 13 respondents (43.3%), and the nutritional status of the children was mostly good with a total of 16 children (53.3%). The results of the Spearman Rank test show that there is no relationship between mother's knowledge about balanced nutrition, mother's attitude about balanced nutrition, mother's actions about balanced nutrition with the nutritional status of the children at Elementary School No. 98 in North City of Gorontalo with each sig value ( 2 tailed ) = 0.387, 0.868, and 0.505.